Adolescent smoking behaviour determinants in the city of Yogyakarta, Indonesia - Wibowo, Marsiana; Sofiana, Liena; Ayu, Suci Musvita; Gustina, Erni; Khoeriyah, Inganatul (International Journal Of Community Medicine And Public Health, 2019)
Background: The increasing number of smokers has an impact on increasing the number of deaths due to smoking-related illnesses. Teenagers are the easiest targets for cigarette marketing, including in the city of Yogyakarta, whose numbers continue to increase. The proper investigation needs to be carried out to determine the determinants that play a role in developing effective interventions to reduce the number of teenage smokers. The purpose of this study was to determine the determinants of smoking in adolescents in The City of Yogyakarta. Methods: This study was a cross-sectional study with senior high school/vocational students’ samples. The sampling technique uses multistage random cluster sampling with Chi-Square analysis. Results: Researchers collected 481 respondents. Variables significantly associated with smoking behavior of senior high school/vocational high school students in Yogyakarta City are knowledge, attitude, self-confidence, family’s role, and peer’s role, while the unrelated variables are teacher’s role and information sources. The RP value of these variables is more than 1, which shows the seven variables are risk factors for adolescent smoking behavior. Conclusions: There is a significant relationship between knowledge, attitudes, self-confidence, the role of family, the role of peers and the smoking behavior of adolescents in Yogyakarta, Indonesia. The role of the teacher and the source of information has no significant relationship with the smoking behavior of adolescents in Yogyakarta, Indonesia. The intervention program for reducing and preventing smoking must pay attention to these variables as a determining factor.